IMPLEMENTATION OF INVESTIGATION GROUP LEARNING MODEL IN IMPROVING THE ABILITY OF WRITING NEGOTIATION TEXT IN VOCATIONAL SCHOOL - Siti Nurjanah; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2020)
Negotiation itself is actually closely related to the daily lives of students. Negotiations are usually carried out by everyone in their daily lives, because negotiating means trying to reach an agreement, in everything. This study implements the investigation group model in the study of negotiating texts. The research objectives are to 1) describe the results of research in the classroom using the investigation group learning model and 2) to describe student learning outcomes. The research method used is an experimental method with a type of non-equivalent control group. The results showed an increase in students with SPSS calculation results was 0.001, meaning that the resulting data was less than 0.05 significance. This means that the instructor writes negotiating texts using the group investigation model is considered successful.